Tantangan Guru Agama Katolik Dalam Meningkatkan Motivasi Belajar Siswa Pada Pendidikan Agama Katolik (Jurnal Pendidikan Agama dan Teologi, 2024)
Motivation to learn for a student is important. With motivation, students are able to participate in the learning process enthusiastically and are able to improve learning achievement and achieve learning goals. However, since the Covid-19 pandemic until now, students' learning motivation has begun to decline, which also affects their learning achievement, achievement of learning goals, and enthusiasm during the learning process. Catholic religious teachers, as educators and motivators, take a role in increasing students' learning motivation. In this effort, teachers experience challenges and obstacles. This article contains an understanding of student motivation, efforts that a Catholic religious teacher can make to increase student learning motivation, and the challenges experienced in these efforts. Writing this article will use the literature review method. This method is carried out by collecting various valid and reliable sources, whether in the form of books, articles, journals, etc. as reference material in writing and collecting information that is appropriate to the material discussed in this article.